Influence of led supplemental lighting on aeroponic potato (Solanum tuberosum L.) minitubers production - Dulay, Alvin C; Somera-Almerol, Carolyn Grace G; Badua, Sylvester A; Fabula, Jonathan V; Mateo, Wendy C (Asian Journal of Agriculture and Rural Development, 2025)
The photoperiod significantly regulates the growth and tuberization of a potato (Solanum tuberosum L.) transplanted inside a greenhouse grown aeroponically. Using a full spectrum LED grow light with 55% red (660 nm), 30% blue (450 nm), 15% other colors (5% of 6500K white, 5% of Infrared 730 nm, 5% of Ultraviolet 380 nm) illuminating 100 μmol/m2/s photosynthetic photon flux density (PPFD) on the granola potato cultivar, a 3-hour lighting supplementation, 6-hour lighting supplementation, and no lighting supplementation (natural daylength) were performed to investigate the effects on the growth and minituber production of potato plantlets. The supplemental lighting enhances height, increases stem diameter, and increases leaf size and the number of lateral stems. Compared to plantlets grown in natural daylight, the quality of the mini tubers increased by 51% in weight, 76% in diameter, and 21% in the average number of mini tubers per plant, offsetting the delayed stolon and tuber initiation. The results of this study suggest that a 3-hour lighting supplementation using full-spectrum LED lights is effective in propagating potato mini tubers. There is no significant difference between the 3-hour and 6-hour lighting supplementation in terms of minituber production; therefore, adopting the 3-hour regimen is more practical.